Selective Atrophy of the Vastus Medialis: Does It Exist in Women With Nontraumatic Patellofemoral Pain?. Issue 3 (March 2021) - Ho, Kai-Yu; Chen, Yu-Jen; Farrokhi, Shawn; Tsai, Liang-Ching; Liao, Tzu-Chieh; Haas, Nicole; Powers, Christopher M.
Background: A commonly cited theory related to the pathomechanics of patellofemoral pain (PFP) states that atrophy of the vastus medialis (VM) muscle leads to lateral tracking of the patella. However, isolated atrophy of the VM or atrophy of the quadriceps muscle group as a whole, has not been consistently reported in this population. Purpose: To compare individual and total quadriceps muscle volumes between women with nontraumatic PFP and women without PFP as measured on magnetic resonance imaging scans. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 52 women with nontraumatic PFP and 64 women without PFP between the ages of 18 and 45 years participated. Magnetic resonance imaging scans of the thigh were obtained from the anterior inferior iliac spine to the tibial plateau. Individual quadriceps muscle cross-sectional area measurements were obtained from each image, and muscle volumes for the VM, vastus lateralis, vastus intermedius, and rectus femoris were calculated. Muscle volume measurements were expressed in absolute values and normalized to body mass. Separate 2-way mixed-factorial analysis of variance (group × muscle) were used to compare absolute and normalized individual muscle volumes between groups. Independent t tests were used to compare absolute and normalized total quadriceps volumes between groups. Results: There was no difference in absolute and normalized individual muscle volumes between individuals with and those without PFP. Additionally, absolute and normalized total muscle volumes did not differ between groups. Conclusion: Our findings do not support the concept of preferential atrophy of the VM or generalized quadriceps atrophy in women with nontraumatic PFP.